(untitled) (Physical Education, Health and Social Sciences, 2025)
Enhancing the technical and professional competencies of agricultural field advisers through in-service training is essential for providing them with the expertise needed to boost agricultural resilience and performance. The current research examines how well in-service training for agricultural advisors in South Punjab, Pakistan, enhances their professional development, job satisfaction, and knowledge and attitude interventions. A standardized questionnaire distributed via Google Docs via email and WhatsApp was used to gather responses from 300 farm advisors from five areas. A Likert scale was used to gauge responses about the usefulness of the training, technical competency, capacity for problem-solving, collaborative behavior, and technological competence. Based on the results, most respondents believe that in-service training is crucial to enhancing their performance, flexibility, and professional development. However, a deficit in ICT capacity development has been observed highlighting the necessity of an integrated digital training paradigm. For the purpose of increasing the effectiveness and information sharing in the agriculture sector, research suggests that the industry implement systematic and relevant training programs that incorporate technological proficiency and practical applications.